Analisis Komparatif dan Implementasi Kebijakan Fiskal pada Negara Indonesia dan Arab Saudi Perspektif Ekonomi Islam - Dede Nurwahidah; Yadi Janwari; Sofian Al-Hakim; Nissa Ayu Marliana (Yayasan Literasi Sains Indonesia, 2025)
This study analyzes the disparity between the ideal concept of Islamic fiscal policy implemented during the Prophet Muhammad's era and the Rightly Guided Caliphs period with its contemporary practice in Muslim countries, focusing on Saudi Arabia and Indonesia. Using qualitative methods and historical-comparative analysis, the research identifies three main differences: (1) the public financial management system, where Baitul Mal has evolved into a modern financial system that is not fully sharia-compliant; (2) state revenue sources, where reliance on zakat, kharaj, and jizyah has shifted to conventional taxation; and (3) welfare distribution mechanisms, which have been reduced to limited social programs compared to the comprehensive Islamic social security system. Additionally, both case study countries have economic development visions—Saudi Arabia's Vision 2030 and Indonesia's 2045 Economic Transformation—that influence their fiscal policies. The factors contributing to this gap include pressures from the global economic system, limitations in implementing sharia in public finance, insufficient in-depth understanding of Islamic fiscal concepts, and the complexity of transitioning from conventional to sharia-based systems. Theoretically, this study contributes to developing an adaptive Islamic fiscal policy model suitable for modern contexts. Practically, it provides policy recommendations to strengthen the implementation of sharia-based fiscal systems in Muslim countries while addressing global challenges and national development needs. slim countries in optimizing the implementation of a sharia-based fiscal system.